Unmasking Vibrio vulnificus: Emerging “flesh-eating bacteria” and its health implications - Galo Guillermo Farfán-Cano (Trends in Infection and Global Health, 2023)
Recent media reports in the USA have raised concerns about dubbing Vibrio vulnificus as the "flesh-eating bacteria," which is traditionally associated with treptococcus pyogenes. This review aimed to explore V. vulnificus as an emerging pathogen, its role in human infections, and its association with necrotizing fasciitis in wound infections. A systematic review was conducted of articles published between 2013 and 2023, focusing on V. vulnificus and its role in human infections. The inclusion and exclusion criteria were rigorously applied. The search  identified 16 articles of which seven studies included in the review, with 77 V. vulnificus-induced necrotizing fasciitis cases reported over the past decade. Demographic and diagnostic data were analyzed, highlighting the need for further research due to regional variations. This comprehensive review highlights the emerging significance of V.vulnificus as a pathogen, particularly in the context of necrotizing fasciitis and emphasizes the need for region-specific research. Understanding V. vulnificus infection is crucial for timely intervention and improved public health outcomes.